PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN LUAS JAJAR GENJANG DAN SEGITIGA DENGAN METODE INKUIRI DI KELAS IV SD - Sy, Monalisa (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research early from fact in elementary school that studed often dominated by the teacher as a source information or conventional, so the students were difficult to know what the teacher said and they can not to show their ideas in the class. The approach that researcher used was qualitative and qualitative approach. The research method used was a action research conducted two cycle, each cycle consist of the activities of planning, acting, observation, and reflection. And data collection method were test and non test. The result showed that : construct of approach can improve the students ability in learning math. It can show from the cognitive mark is 60,88 to 75,15, affective mark is 65,42 to 75,53, and psychomotor mark is 67,36 to 79,85 in the second cycle. Kata kunci : hasil belajar, metode, pembelajaran, metode inkuiri